Adding Only One Priority Rule Allows Extending CIP Rules to Supramolecular Systems. Issue 5 (20th March 2015) - Alkorta, Ibon; Elguero, José; Cintas, Pedro
Abstract There are frequent situations both in supramolecular chemistry and in crystallography that result in stereogenic centers, whose absolute configuration needs to be specified. With this aim we propose the inclusion of one simple additional rule to the Cahn‐Ingold‐Prelog (CIP) system of priority rules stating that noncovalent interactions have a fictitious number between 0 and 1. Chirality 27:339–343, 2015. © 2015 Wiley Periodicals, Inc.